Acesso à justiça e práticas colaborativas: mudança cultural no ensino jurídico para efetivação da garantia constitucional da duração razoável do processo - Melo, Fernanda Banhos Carneiro (2023)
This dissertation analyzes the perspective of access to justice through the self-composed means of conflict resolution, based on the discipline of Resolution nº 125/2010of the National Council of Justice (CNJ), which instituted the National Judiciary Policy for the Appropriate Treatment of Conflicts and Interests within the scope of the Judiciary. Despite extensive legislation that sought to facilitate access to justice and promote the effectiveness of this constitutional guarantee, the majority of the Brazilian population is not aware of all the existing means at their disposal for resolving disputes, always seeking first and foremost place the Judiciary, which entails a large number of demands that enter the state machine every year, as opposed to a smaller number of finalized processes, leading to a longer duration of the processes, as well as to the dissatisfaction and distrust of the population in relation to the Judiciary. Thus, the primary focus of the present work is to examine the barriers to effective, fair, and timely access to justice, presenting the institute of Collaborative Practices as an alternative to conflict resolution through the Judiciary, an extrajudicial and interdisciplinary means of conflict resolution, capable of giving effectiveness to the guarantee of access to justice, bringing satisfaction to the parties, regardless of the Judiciary. Still, it analyzes the extent to which Brazilian legal education contributes to the lesser use of self-compositional means in dispute resolution, due to the prevalence of Cartesian legal dogmatics of law enforcement and the absence of training that contemplates the vicissitudes of social realities, economic and cultural. Finally, the role of the lawyer is observed in his social role as an agent of transformation of reality and conflict resolution, a professional indispensable to the administration of justice. It is concluded that the Judiciary still holds the almost exclusivity of the solution of the conflicts placed for its analysis, with a scarce use of the autocompositive means of conflict resolution, especially the Collaborative Practices, which mitigates the effectiveness of the constitutional guarantees of the access to justice and the reasonable duration of the process, especially in view of the demanding culture that prevails in the Brazilian legal system, reinforced by legal teaching that prioritizes dogmatism.